Influence of Health Referral Systems on Adolescent Sexual and Reproductive Health Service Utilization in Kajiado County, Kenya - Aluda, Wilfrida; Njoroge, Kezia; Mapesa, Job (Journal of Health, Medicine and Nursing, 2025)
Purpose: Adolescent Sexual and Reproductive Health (ASRH) in Kajiado County, Kenya, is hindered by early marriages, cultural practices, and limited healthcare access. The pastoralist communities face unique challenges, increasing risks like unintended pregnancies and maternal mortality. Despite efforts to improve access, gaps in ASRH service utilization persist. This study examines the influence of referral systems on ASRH service use among adolescent girls in Kajiado County. Methodology: A mixed-method design assessed the influence of referral systems on ASRH utilization among adolescent girls in Kajiado County. Data collection took place from December 2023 to March 2024. Quantitative data from 422 girls were analyzed using SPSS version 26, while qualitative data from 5 FGDs, 15 IDIs, and 15 KIIs were analyzed thematically using NVivo. Findings: Only 15.8% of adolescents used ASRH referral systems. Trust (78.6%), confidentiality (74.2%), and accurate information (71.5%) were key facilitators. Married adolescents were 32.1% less likely to utilize referrals (p < 0.05), and those with primary education were 45.3% less likely (p < 0.01). Positive outcomes included 83.4% reporting improved ASRH knowledge and 79.2% better contraceptive access. Barriers included communication gaps (62.7%) and limited provider awareness. Unique Contribution to Theory, Practice and Policy: The study identifies barriers such as poor communication, limited provider awareness, and socio-demographic disparities hindering ASRH service utilization. Positive outcomes, including improved knowledge and contraceptive access, suggest the potential of effective referral systems. Strengthening trust, confidentiality, and targeting vulnerable groups is crucial for improving ASRH referral pathways. Limitations included the small sample size and limited geographic scope.